M-Polynomial and Degree-Based Molecular Descriptors of Certain Classes of Benzenoid Systems. (3rd July 2022) - Julietraja, K.; Venugopal, P.; Prabhu, S.; Liu, Jia-Bao
Abstract: Benzenoid systems are a notable class of polycyclic aromatic compounds which have applications ranging from household materials to advanced fields like nanotechnology. Hence, the study of their fundamental properties, like observed bioactivities, carcinogenicity, toxicity, and other significant characteristics, have fascinated theoretical chemists for quite a long time. From this perspective, the topological descriptors of these networks, facilitate the prediction of their molecular properties through quantitative structure-activity (QSAR) and structure-property relationships (QSPR) methods. This article focusses on the computation of analytical expressions for nine degree-based topological descriptors using the M-polynomial, for three benzenoid structures: convex benzenoid system, hexabenzocoronene (HBC), and hexa-cata-hexabenzocoronene (cHBC). Besides, the expressions for a few recently developed indices are also calculated using edge-partition techniques. These derived indices are then compared graphically based on their numerical values. This analysis of degree-based descriptors for these structures can lay the groundwork for future researchers to discover and explore new benzenoids and their properties.